The Role of Persian Historical Bath in City and Urban Life - Kermani, Fariba (Journal of History Culture and Art Research, 2017)
The importance and necessity of bath and its status in city, the role of bath in social relations, its strong tie with religious and indigenous traditions and costumes, its significant relationship with medicine and medical approaches and its presence in most of important stages of life are examples of features that place the bathes in special position. Traditional requirements and health related approaches positioned washing and bathing as one of the Iranian customs accompanying the man from birth, to even after death. Obviously such a widespread and subtle phenomenon has been manifested in all different aspects of Iranian people’s social life. Accordingly, the location of baths in the city was determined based on social relations and environmental requirements and location of the water supplying system. This study answers these questions: What has been the role and status of the Iranian historical bathes in cities and people’s life? And based on that how have been the distribution and substitution of baths? The results suggest that bath had an important role more than other public buildings and even in many cases it had been an assistant to them.